Manual for the construction and operation of a natural cassava drying plant - Ospina Patiño, Bernardo; Best, R. (International Center for Tropical Agriculture, 1981)
The principal aspects that should be considered when constructing the min. infrastructure necessary for a cassava plant with a 500 m(2) drying surface and a capacity to dry 6 t/wk. are described in detail, in addition to the equipment (scales, chipper, and motor), and implements and tools (wheelbarrows, rakes and shovels for collecting chips, plastic sheets, and packing materials, among others). The steps and materials involved in the construction of the drying surface, chipping area, and storage warehouse, and in the fencing off of the drying surface, are specified. Organizational and operational aspects of the plant are discussed as well as plant output. Factors determining the appropriate dimensions of a cassava root drying plant, including cassava production in the area, prevailing climatic conditions, and amount of dried cassava to be produced, are indicated. Diagrams of the infrastructure of a natural drying plant, its cost as well as others involved in the process, are given. (CIAT)